Peningkatan Jumlah Apoptosis Airway Smooth MuscleBerhubungan dengan Peningkatan + Jumlah Sel T CD8 pada Model Mencit Asma - Setiawati, Dessy; Kusuma, HMS Chandra; Kusworini, Kusworini (Jurnal Kedokteran Brawijaya, 2009)
Airway  remodeling  is  an  important  thing  in  asthma.The  increase  of  airway  smooth  muscle  mass  is  a prominent  feature  of  asthmatic  airway  remodeling.  The importance  role  of  airway  smooth  muscle cell  (ASM) + apoptosis in airway remodeling is unknown.T cell also had important role in asthma, whereas CD4 T cell +role  in  airway  remodeling  has  already  known,  but  how  CD8   T cell  role  in  airway  remodeling  is  still  unclear.  A randomized  control  group experimental study  used Balb/c mice, that  categorized into  2 groups: asthma and control.  Asthma group was sensitized by ovalbumin intraperitoneally  in  day 0 and 14, followed  by inhalation +every  2-3  days  for  6  weeks.  In  week  8,  all  of  mice  were  terminated.   The  expression  of  CD8   T  cell  lymphocyte was  examined  through  immunohistochemistry  method,  whereas  ASM  apoptosis  by  TUNEL  method. Independent sample t-test and spearman test was used in statistical analysis with confident interval 95%. The  bronchioli  and  lungs  specimens  were  obtained  from  18  mice  (9  in  each  group).  Case  goup  had  significant +increase  in  the  amount of ASM apoptosis and expression of CD8   T cell lymphocyte  (p=0.000;  p=0.001). +There was also positif correlation between  ASM apoptosis and expression of CD8   T cell (r=0.37,  p=0.065). +We  conclude  that  increasing  ASM  apoptosis  has  a  relationship  with  increasing  CD8   T  cell+Keywords:  asthma,  mice,  ovalbumin,  ASM  apoptosis  and  CD8   T  cell